Impact of Rye Cover Crop on Pigweed Seed Viability - Holguin, Kimberly; Woitaszewski, Lily; Lancaster, Sarah; Dille, Anita (My University, 2023)
Palmer amaranth (Amaranthus palmeri) and waterhemp (Amaranthus tuberculatus) are the two pigweed species most prevalent in Kansas. They are difficult to manage because they are resistant to herbicide applications. Cereal rye (Secale cereale) is a grass notable for its ability to hold soil in place against erosion. This study was conducted to test a cereal rye cover crop’s ability to deplete the presence of Palmer amaranth and waterhemp in the seedbank when buried compared to those with no cover crops present. Fifty seeds in wire mesh packets were buried in soybean fields at seven different sites in the states of Indiana, Kansas, Missouri, North Dakota, and Wisconsin. Packets were removed at three intervals and seed viability was determined by cleaning the wire mesh packets with a water and bleach solution followed by germination in petri dishes. If samples showed zero germination for three days, seeds were then squished and observed under a microscope. This determined whether seeds were dormant or nonviable. Seed viability data will be discussed and results will provide insight into whether cereal rye cover crop may have an impact on depletion of pigweed seeds in the north central region of the United States.
Keywords: Cover crop; Weed control; Herbicide resistance; Cereal rye; Seed viability; USDA NIFA 2019-67032-29071